Energy system development in the weight room: Incorporating prescribed rest periods for NCAA men's basketball players - Bender, B. (Strength and Conditioning Journal, 2019)
Training programs often vary sets and reps to achieve different training goals. Rest is not often programmed within an annual training cycle but can be prescribed in resistance training sessions to further develop energy systems demanded by sport. Specifically, basketball includes intermittent periods of moderate to high intensity, deriving most of its energy from the adenosine triphosphate-phosphocreatine and anaerobic glycolytic systems. By identifying specific work:rest ratios in basketball, strength coaches can prescribe logical rest periods within a weight training session. Not only will this enhance overall energy system development, but will also provide more structure to strength training routines.